Laplace Distribution Based Online Identification of Linear Systems With Robust Recursive Expectation–Maximization Algorithm - Chen, Xin; Zhao, Shunyi; Liu, Fei; Tao, Chongben (IEEE transactions on industrial informatics, 2023)
The robust online identification problem of linear systems is considered in this article using a faster robust recursive expectation–maximization (RREM) framework. To improve the convergence rate, the outliers, which would deteriorate the identified models, are accommodated with a Laplace distribution instead of Student's [Formula Omitted]-distribution. Then, the recursive transformation of the maximum likelihood function is realized with a recursive [Formula Omitted]-function. The extensively recognized autoregressive exogenous (ARX) models are used for the description of general linear systems. As a result, the unknown parameters, including the regression coefficient vector of the ARX models, the variance of the noise without outliers, and the scale parameter of the Laplace distribution, are determined in a recursive manner. The performance of the proposed approach is tested with a simulated continuous fermentation reactor system example and a coupled-tank experiment.